Observation of Canna lily for Phytotechnology in Constructed Wetland - Ram Babu Pachwarya; Euis Nurul Hidayah; Rizka Novembrianto; Yuliatin Ali Syamsiah (Nusantara Science and Technology Proceedings)
The application of sewage treatment in New Delhi should implement the treatment processes, which are easy to be operated and is not costly operational and avoid the complexity of the operating system of STP. The renewed interest in alternative onsite treatment technology by using a constructed wetland (CW). Canna lily, an ornamental plant that has an aesthetic value, is very suitable for an alternative plant for a constructed wetland. This study aims to observe the ability of canna lily for phytotechnology implementation in a constructed wetland. This study is known as a range-finding test (RFT), which served as a preliminary test. Observation is conducted by preparing variation concentration of wastewater; 25%; 50%; 75%; 100% and 0% as control, which was injected into the wetland. CW (60 cm long, 60 cm wide and 60 cm deep) contained gravel medium height 25 cm with a wastewater volume 3 L. Observation measured the height of the plant, the color of the leaf, and DO, and BOD concentration. The observation was conducted for about 25 days, in term of 15 days for range finding test and 10 days for acclimation. The results show that Canna lily could grow well, though it has some part of the withered leaf, reach height significantly, and indicated decreasing concentration of organic parameters. It is conjectured that Canna lily is very possible for a constructed wetland application.